Environmental Vision of Saija’s Characters in the Kelomang Novel by Qizink La Aziva - Ghulamin Khalim Subagiyo; Tommi Yuniawan (Yayasan Keluarga Guru Mandiri, 2022)
In the current literary realm, literary texts that present natural destruction events implicitly or explicitly are called apocalyptic literature. The main characteristic of apocalyptic literature is the emergence of characters who have heroic characters. The Kelomang novel written by Qizink La Aziva was chosen because it is one of the novel texts that does not only make the environment the setting, but also makes the environment a part of the story. The story in the Kelomang novel is characterized by apocalyptic. This study aims to find the environmental vision of Saija's character in the Kelomang novel by Qizink La Aziva. This study uses an ecocritical approach to apocalyptic literature. The data source of this research is the text of the Kelomang novel by Qizink La Aziva published by PT Gramedia Pustaka Utama in Jakarta in 2016. The data in this study is a text fragment of the Kelomang novel by Qizink La Aziva which allegedly contains Saija's environmental vision. The result of this research is that Saija has a vision of the environment to save the environment from the increasingly severe impacts of environmental damage, especially in his area, namely Banten.